Improving the Performance Measurement Using Overall Equipment Effectiveness (OEE) in Borouge - ALMUTAWA, MUBARAK (2023)
A hierarchy of measurements called Overall Equipment Effectiveness (OEE) is used in the industrial sector to gauge the performance of production machines. OEE measurement is a crucial machine performance tool that assesses availability, performance, and quality rate. It is inspired by Total Productive Maintenance (TPM). This study was conducted in Al Borouge company is a prominent petrochemical firm that offers unique and new polyolefin solutions for the energy, mobility, advanced packaging, infrastructure, healthcare, and agricultural industries. The main issue found relating to the two extruder production lines productivity was where availability and quality show a significant decrease. Thus, data were collected for 12 months from the two extruders and analysed using Microsoft Excel Software to determine the value of the output table and presented graphically. This study starts by calculating the availability, performance rate, and rate of quality, then listing the six biggest losses that happen in order to determine the achievement of Overall Equipment Effectiveness (OEE) value. According to the findings, the average OEE on a first extruder is 95%, and second extruder is 91%, the value is higher than the world's ideal OEE standard value of > 85%. But This research needs to make improvement on these components to increase the value of OEE. Three of the six major losses downtime losses, speed losses, and quality losses were grouped together. The findings show there is no set up/adjustment and speed losses. Moreover, breakdown losses were 2.2% for first extruder and 6.06% for second extruder, and decreased quality losses were 1.28% for first extruder and 2.8% for second extruder for the study of six significant losses (which became three big losses due to speed losses and set up/adjustment do not exist).